Connecting the pieces of the puzzle toward sustainable organizations A framework integrating OM principles with GSCM - Sarkis, Joseph; Bai, Chunguang; Lopes de Sousa Jabbour, Ana Beatriz [UNESP]; Chiappetta Jabbour, Charbel Jose [UNESP]; Sobreiro, Vinicius Amorim (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to propose a framework integrating the Hart and Milstein (2003) strategies for organizational sustainable development (SD) with the ideas of Kleindorfer et al. (2005) on sustainable operations management (SOM), which requires guidance of green supply chain management (GSCM). Design/methodology/approach - The construction of the framework was based on previous studies that discussed synergies between operations management principles with environmental bias and studies on adoption of GSCM practices. Findings - The proposed framework guides managers to reconcile operations management practices/principles that are already being implemented in organizations with an environmental perspective because these practices sustain organizations to simultaneously reach SOM and SD. Originality/value - The paper presents a framework that provides guidance on how organizations can seek sustainability in their operations, considering that articles on the topic of sustainability have not been developed with this specific focus.
Keywords: Sustainable development; Operations management; Sustainable operations; Green supply chain management